A Comparative Evaluation of Cross Linked Starch Urea-A New Polymer and Other Known Polymers for Controlled Release of Diclofenac - CHOWDARY, K.P.R.; UDAYA CHANDRA, D. (Asian Journal of Chemistry, 2010)
The objective of the present investigation is to synthesize crosslinked starch-urea, a new starch based polymer and to evaluate its application for controlled release of diclofenac. The release retarding and rate controlling efficiency of cross-linked starch-urea was also compared with that of other known polymers. Cross-linked starch-urea polymer was synthesized by gelatinization of starch in the presence of urea and calcium chloride. Matrix tablets each containing 100 mg of diclofenac were formulated employing cross-linked starch-urea in different concentrations in the formula and other polymers such as methyl cellulose (MC), hydroxy propyl methyl cellulose (HPMC, K15M), sodium carboxy methyl cellulose (sodium CMC) and sodium alginate (SA) at 1:1 ratio of drug:polymer by wet granulation method and the tablets were evaluated. Diclofenac release from the matrix tablets formulated employing crosslinked starch-urea was slow, spread over 24 h and depended on the concentration of cross-linked starch-urea polymer in the tablets. Non- Fickian diffusion was the drug release mechanism from these matrix tablets. Diclofenac release from the matrix tablets (F3) formulated employing 66 % cross-linked starch-urea was similar to that from voveran SR tablets, a commercial SR formulation of diclofenac. The order of increasing release retarding effect observed with various polymers was HPMC, K15M > cross-linked starch-urea > MC > sodium CMC > sodium alginate. Cross-linked starch-urea was found to be a better release-retarding polymer than sodium alginate, sodium carboxy methyl cellulose and methyl cellulose. Cross-linked starch-urea and hydroxy propyl methyl cellulose were found more suitable for controlled release application. Diclofenac CR tablets for once-a-day (24 h) administration could be designed employing cross-linked starch-urea.